Analysis of Students’ Drawback in Writing Mini Research in 2020 Pasundan University Curriculum Setting - Alwasilah, Senny Suzanna (Journal of Education Research, 2024)
Acquiring proficient writing abilities is essential, as it allows students to refine the other three language proficiencies: reading, listening, and speaking. These proficiencies are vital for bolstering students' groundwork in academic writing. this study aims to analyze the students' drawbacks in writing a mini research paper. The participants were college students at a university in Bandung. Writing samples and interview used as data analysis. The findings underscore the pressing need for students to bolster both their writing proficiency and their grasp of research writing frameworks. As the cornerstone of academic communication, effective writing skills are essential for students to convey their ideas with clarity and coherence.